Trust Central Eases Funding Decisions With Data - Munoz, Marden F; Sylvestre, Stephanie (International Journal of Population Data Science, 2018)
The Children’s Trust is a local government taxing authority that uses property tax dollars to fund programming for Miami-Dade County children and families. To become more efficient, Trust Central was created and now automates our full business cycle. Data flow is solicitation → contracting → program metrics → solicitation. Agencies apply for funding, contract to provide services, report their progress. Their progress is used to determine future solicitation criteria. Data automatically flows from one module to another. Trust Central allowed us to move from using 5 data points to make funding decisions to 24 data points. We were able to look across our various initiatives to ensure that our funding decisions were equitable. Funding decisions were backed by data and easy to share with applicants. We created context and communicated funding decisions in a way that reduced emotional conflicts and appeals. As a reference point, we had 96 appeal meetings last funding cycle - this funding cycle no appeal meetings and only 19 review meetings; a cost savings of 15,850 in meetings. Another reference point, we spent 1 week reviewing data to make funding decisions last funding cycle - this funding cycle we spent 4 weeks reviewing data in a more meaningful and valuable way. We made 68M in funding decisions without any negative feedback from the community. Our relationship with the community pivoted from negative to positive. This is a first for us! We are now positioned to be a mentor for both governmental and non-governmental funders.